Parental attention patterns to ask children to study in the Covid-19 pandemic - Buhaerah Buhaerah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This research aims to find out more about the parental engagement in children's online learning during the Covid-19 pandemic. Patterns of Parental Attention to Interest in Children Learning Mathematics in the Covid-19 Pandemic Period. This research is useful for students, teachers/parents, and future researchers. This type of research is Ex post facto research using a quantitative approach with the data collection instrument using a questionnaire. The data analysis technique is using descriptive analysis and inferential analysis. The sample of this study is class VII.4 taken from the population using cluster random sampling technique by choosing one class at random from the whole class. VII is there. The results showed that: the pattern of attention carried out by parents to their children was categorized as very low, referring to the interpretation level. Students' interest in learning mathematics during the pandemic is in the very low category. The results showed that the pattern of parental attention during the Covid-19 pandemic on students' interest in learning mathematics showed that there was a positive and significant relationship between the pattern of parental attention on students' interest in learning mathematics during the pandemic, proven by the calculated value of 20 samples, which showed that the pattern of attention parents have a strong relationship with.